Wyzwania diagnostyczne cyklicznego zespołu Cushinga u 15-letniej dziewczynki - An, Melissa; Hendricks, Landon; Bachrach, Bert (Pediatric Endocrinology Diabetes and Metabolism, 2020)
Cyclical Cushing’s syndrome (CS) is a rare disorder in which cortisol secretion is cyclical and intermittent. This phenomenon makes for a challenging diagnosis, as patterns of cycling can vary widely among patients and as patients with cyclical CS do not exhibit unique clinical features compared to those without cycling. Current research suggests that cyclical CS may be present in approximately 15% of adult cases, with an even lower reported prevalence in the pediatric population. In this case study, we describe a 15-year-old female with obesity and hypertension who was then diagnosed with cyclical CS after we pursued additional screening tests of urine creatinine and 24-hour urine cortisol, dexamethasone suppression tests, bilateral inferior petrosal sinus sampling, as well as MRI. We discuss the vari-ous diagnostic modalities in the challenging diagnosis of cyclical CS as well as the importance and modalities of post-operative monitor-ing in this patient population. From this case study, we emphasize that when CS is suspected and initial screening tests are negative, clinicians should be aware of the cycling phenomenon of CS in order to consider performing additional screening tests.